Strategic Capabilities in Services: Analysis of the Relationship between Entrepreneurial Orientation, Innovation Culture, and Service Innovation Performance - Shum León, Andrés; De Montreuil Carmona, Linda Jessica (LACCEI, 2025)
This study examines the relationship between Entrepreneurial Orientation, Innovation Culture, and Service Innovation Performance, and their combined effect on organizational performance in service firms. Drawing from dynamic capabilities theory, we propose and empirically test a hierarchical reflective-reflective model using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the disjoint two-stage approach. The quantitative research involved a survey of 318 managers and decision-makers from service-oriented companies in Costa Rica. Entrepreneurial orientation and innovation culture were modeled as second-order constructs composed of validated dimensions. The measurement model showed adequate reliability and convergent validity, while the structural model confirmed entrepreneurial orientation positive influence on service innovation performance both directly and indirectly through innovation culture. Additionally, service innovation performance significantly impacted perceived organizational performance. Among entrepreneurial orientation dimensions, innovation and proactiveness showed the strongest effects, whereas innovation culture was primarily explained by innovation-oriented behaviors and communication practices. Findings provide empirical evidence of the synergistic role between entrepreneurial orientation and innovation culture in enhancing service innovation and highlight the strategic importance of aligning entrepreneurial mindset with innovation-supportive organizational culture.